Empirical Facts of Educational Chances for Women in Islamic World: Past and Present - Ja'far, Handoko; Rigo, Taufik (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2017)
This article explores educational opportunities in the early period of Islam until the 13th century, which shows the significant role of women in education. It can be argued that the role of women in education can be traced not only in certain areas of religious knowledge but also in the patronage of education and even in determining the political policy of the government. Unfortunately, compared to the next period until the 21st century, policy concerning education has recently turned to unfair treatment such as marginalization, exclusion, and even deprivation. What is surprising is that the reasons for the genitals, which deprive women of their right to participate in education, casually occurred. In other cases, socio-cultures are restricting their access to education. The factual errors on educational thoughts for woman here are explicitly used as an empirical description in this study, while its purpose is to demonstrate the shift in the treatment of female education. The result expected in this study is to reach the historical footprint of Islamic education and ensure inappropriate reasons, such as genital terms, used and abused as arguments for not allowing woman to get education.Artikel ini mengeksplorasi peluang pendidikan pada periode awal Islam hingga abad ke-13 yang menunjukkan peran penting wanita dalam pendidikan. Dapat dikatakan bahwa peran perempuan dalam pendidikan dapat ditelusuri tidak hanya di bidang pengetahuan agama tertentu tetapi juga mereka terlibat dalam patronase pendidikan dan bahkan terlibat dalam penentuan kebijakan politik pemerintah. Sayangnya, dibandingkan dengan periode berikutnya hingga pada abad ke-21, kebijakan penanganan pendidikan akhir-akhir ini berubah menjadi perlakuan tidak adil seperti marginalisasi, eksklusi, dan bahkan deprivasi. Satu hal yang mengejutkan adalah perempuan dianggap sebagai aurat dan dijadikan alasan untuk mencabut hak mereka untuk berpartisipasi dalam pendidikan terjadi begitu saja. Kasus lainnya, sosio-budaya membatasi akses perempuan untuk berpendidikan. Kesalahan faktual pada pemikiran pendidikan bagi perempuan sebagaimana tersebut, secara eksplisit digambarkan sebagai deskripsi empiris dalam penelitian ini sementara tujuan penelitian adalah untuk menunjukkan pergeseran perlakuan atas pendidikan perempuan. dengan mencapai jejak historis pendidikan Islam dan memastikan tidak tepatnya penggunaan alasan seputar aurat dan penyalahgunaannya sebagai argumen untuk tidak mengizinkan perempuan mendapatkan pendidikan.